Polygenic risk scores distinguish patients from non‐affected adult relatives and from normal controls in schizophrenia and bipolar disorder multi‐affected kindreds. Issue 3 (28th November 2017) - Boies, Sébastien; Mérette, Chantal; Paccalet, Thomas; Maziade, Michel; Bureau, Alexandre
Abstract : Recent studies have used results on SNP association with schizophrenia (SZ) and bipolar disorder (BD) to create polygenic risk scores (PRS) discriminating non‐familial unrelated patients from controls. Little is known about the role of PRS in densely affected multigenerational families. We tested PRS differences between affected SZ and BD family members from their non‐affected adult relatives (NAARs) in Eastern Quebec Kindreds and from controls. We examined 1227 subjects: from 17 SZ and BD kindreds, we studied 153 patients (57 SZ, 13 schizoaffective, and 83 BD) and 180 NAARs, and 894 unrelated controls from the Eastern Quebec population. PRS were derived from published case‐control association studies of SZ and BD. We also constructed a combined SZ and BD PRS by using SNPs from both SZ and BD PRS. SZ patients had higher SZ PRS than controls ( p  = 0.0039, R 2  = 0.027) and BD patients had higher BD PRS than controls ( p  = 0.013, R 2  = 0.027). Differences between affected subjects and NAARs and controls were significant with both SZ and BD PRS. Moreover, a combined SZ‐BD PRS was also significantly associated with SZ and BD when compared to NAARs ( p  = 0.0019, R 2  = 0.010) and controls ( p  = 0.0025, R 2  = 0.028), revealing a SZ‐BD commonality effect in PRS at the diagnosis level. The SZ and the BD PRS, however, showed a degree of specificity regarding thought disorder symptoms. Overall, our report would confirm the usefulness of PRS in capturing the contribution of common genetic variants to the risk of SZ and BD in densely affected families.